Studies on Homalomeneae (Araceae) of Borneo III: The helophytic Homalomena of Sunda - Wong, Sin Yeng; Boyce, P.C; Fasihuddin Badruddin, Ahmad (Singapore Botanic Garden, 2011)
An account of the helophytic Homalomena in Sunda is presented. Two species are recognized: H. expedita A.Hay & Hersc. and H. rostrata Griff., neither novel. Homalomena expedita is so far endemic to Sarawak, where it is known from three widely separated sites. Homalomena rostrata is widespread from Sumatera through Peninsular Malaysia to Borneo, and onwards to Maluku (Pulau Ceram). Throughout its range H. rostrata is morphologically plastic, such that it has accrued a considerable synonymy, proposed here: Homalomena beccariana Engl., H. ensiformis Alderw., H. miqueliana Schott, H. miqueliana var. truella Alderw., H. paludosa Hook.f., H. propinqua Schott, H. raapii Engl., H. sagittifolia Jungh. ex Schott, H. sagittifolia var. angustifolia Furtado, H. sagittifolia var. pontederiifolia Ridl. (including homotypic H. ridleyana Engl.), H. sagittifolia var. sumatrana Alderw., H. teysmannii Engl., and H. triangularis Alderw. An overview of the occurrence of helophytism in Araceae, together with speculations on the evolution of helophytism in Homalomena, a key to the species, and illustrations of both species are presented.